EphA2-Receptor Targeted PEGylated Nanoliposomes for the Treatment of BRAFV600E Mutated Parent- and Vemurafenib-Resistant Melanoma - Yige Fu; Drishti Rathod; Ehab M. Abo-Ali; Vikas V. Dukhande; Ketan Patel (MDPI AG, 2019)
The clinical outcomes of malignant melanoma have improved with the introduction of mitogen-activated protein kinase kinase (MEK) inhibitors. However, off-target toxicities of the MEK inhibitor trametinib (TMB) often result in dose interruption and discontinuation of therapy. The purpose of this study was to anchor a physically stable EphrinA1-mimicking peptide known as YSA (YSAYPDSVPMMS) on TMB-loaded PEGylated nanoliposomes (YTPLs), and evaluate them in BRAFV600E-mutated parent cells (lines A375 and SK-MEL-28) and vemurafenib-resistant cells lines (A375R and SK-MEL-28R) in melanoma. TMB-loaded PEGylated liposomes (TPL) functionalized with nickel-chelated phospholipids were prepared using a modified hydration method. The hydrodynamic diameter and zeta potential values of optimized YTPL were 91.20 ± 12.16 nm and -0.92 ± 3.27 mV, respectively. The drug release study showed TPL did not leak or burst release in 24 h. The hemolysis observed was negligible at therapeutic concentrations of TMB. A differential scanning calorimetry (DSC) study confirmed that TMB was retained in a solubilized state within lipid bilayers. YTPL showed higher intracellular uptake in parental cell lines compared to vemurafenib-resistant cell lines. Western blot analysis and a cytotoxicity study with the EphA2 inhibitor confirmed a reduction in EphA2 expression in resistant cell lines. Thus, EphA2 receptor-targeted nanoliposomes can be useful for metastatic melanoma-specific delivery of TMB.